ANALISIS PENGARUH CAR, NPF, DAN FDR TERHADAP ROA BANK UMUM SYARIAH - Lukman Hakim; Mutia Pamikatsih; Hatta setiabudi (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
During the observation period, the purpose of this study is to ascertain how return on assets (ROA) in Islamic commercial banks is affected by the financing to deposit ratio (FDR), non-performing financing (NPF), and capital adequacy ratio (CAR).48 purposeful samples taken from Islamic Commercial Banks between 2017 and 2020 comprise the study's population. This study employs the classical assumption test, which consists of four tests: the Normality test, the Multicollinearity test, the Heteroscedasticity test, and the Autocorrelation test. In addition to the Classic Assumption test, this study employs the t test, also known as a partial test, and the F test, either individually or in combination. The results of this study found that the Capital Adequacy Ratio (CAR) variable which has a Sig value does not affect return on assets, while Non Performing Financing (NPF) has a Sig value which affects return on assets of 0.000 and the Financing to Deposit Ratio (FDR) which has a value of 0.297 is above 0.05. Return on assets (ROA) this year can be predicted with these three variables. research, and the remaining 33.4% is influenced by non-research factors.